Climate Change Impact On Rice Productivity Using FAO AquaCrop Model: A Case Study in Lampung - Priatama, Rizki; Katarina Manik, Tumiar; Benyamin Timotiwu, Paul; Pramono, Eko; Alimuddin (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2025)
Climate change impacts global food productions, but its local effect on rice production, particularly on monsoon dominated regions remain less understood. Here, we assess climate change impact on rice production situated on Lampung Province, as one of the largest rice productions in Indonesia. The FAO AquaCrop model was used to predict rice productivity, incorporating climate projections from the CMIP5 model under medium (RCP 4.5) and high (RCP 8.5) emission scenarios. We simulated the model for fifteen locations representing districts in Lampung Province. Our results show that by 2050, the decreased rainfall is projected during the dry season and early rainy season, but the average monthly temperatures and evapotranspiration rates are expected to increase across all districts. AquaCrop simulated an increased rice productivity by +0.25 and +0.74 tons/ha for both scenarios in April planting season, but it decreased by -0.41 and -0.75 tons/ha in November planting season due to water stress. This research is important to provide a deeper understanding of the impact of climate change on rice productivity in Lampung Province. These findings highlight the need for adaptive strategies to sustain rice production under future climate conditions.